2018
DOI: 10.1021/acs.jchemed.8b00392
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Microplastics in Soil and Sediment in an Undergraduate Environmental Chemistry Laboratory Experiment That Promotes Skill Building and Encourages Environmental Awareness

Abstract: Environmental pollution is both a worldwide and a local issue, and microplastic pollution in particular is receiving increased attention due to its prevalence and bioaccumulation potential affecting the food chain. This laboratory experiment uses current, research-based methods such that the students can determine the extent of microplastic pollution in local soil samples. This laboratory experiment can be used as either a 2 or 3 week mini-research-project for first-year undergraduate students in either an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…I chose to require all the experiments for the remainder of my course to be inquiry-based as we moved to remote learning. It has been previously shown that inquiry-based environmental sampling and analysis laboratory experiments have been successful in not only keeping the students’ engagement higher, but that they can also increase the students’ understanding of the connection between science and everyday life . I found similar results during our shift online, as many students utilized their knowledge of their environment (i.e., limestone quarries, waterfalls) to guide their projects based on their own personal observations and interests.…”
Section: Concluding Thoughtssupporting
confidence: 58%
“…I chose to require all the experiments for the remainder of my course to be inquiry-based as we moved to remote learning. It has been previously shown that inquiry-based environmental sampling and analysis laboratory experiments have been successful in not only keeping the students’ engagement higher, but that they can also increase the students’ understanding of the connection between science and everyday life . I found similar results during our shift online, as many students utilized their knowledge of their environment (i.e., limestone quarries, waterfalls) to guide their projects based on their own personal observations and interests.…”
Section: Concluding Thoughtssupporting
confidence: 58%
“…Many of the issues associated with these differing approaches are discussed, but it can be argued that other aspects should also be considered in establishing a single methodology. One of the benefits of microplastics study is that the topic is quickly understandable for most people and can be the focus both for specialized research as well as practically applied by students (Rowe et al 2019). This may be lost to some degree once a particular methodology is established since some of equipment being developed or employed in a microplastic study can easily be outside the financial capability of some groups.…”
Section: Methodology Considerationsmentioning
confidence: 99%
“…For example, Rowe and co-workers recently reported a multi-week research project tasking first-year students with investigating the presence of microplastics in soil and sediment. [20] A postlaboratory survey indicated that this experience increased student awareness of scientific research, microplastic pollution, and the potential impact on the environment, thereby aligning with TLO 1. In addition, this endeavour had a positive impact on the chemistry-specific learning outcomes.…”
Section: Introductionmentioning
confidence: 93%
“…[21] Through direct observation and student interviews, the authors found similar learning benefits to those described by Rowe and co-workers. [20] While we have provided some specific examples in the area of chemistry, there are few published examples reported. Furthermore, concerns have been raised over ethical considerations for citizen science.…”
Section: Introductionmentioning
confidence: 99%